2020
DOI: 10.1016/j.ijsu.2020.05.032
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of the novel SARS-CoV-2 outbreak on surgical oncology - A letter to the editor on “The socio-economic implications of the coronavirus and COVID-19 pandemic: A review”

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
0
5
0
1
Order By: Relevance
“…A global survey of 351 cancer centres, conducted in April/May 2020, reported that 88.2% of centres reduced their usual care, and the most common reason was due to precautionary measures [ 10 ]. However, centres in Canada and other countries are also reporting fewer referrals from general practitioners to oncology providers for diagnosis or treatment [ 8 , 34 , 35 ]. This may mean Ontario could see a reduction in treatment volumes and the need for the interim funding measures in the coming months may be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A global survey of 351 cancer centres, conducted in April/May 2020, reported that 88.2% of centres reduced their usual care, and the most common reason was due to precautionary measures [ 10 ]. However, centres in Canada and other countries are also reporting fewer referrals from general practitioners to oncology providers for diagnosis or treatment [ 8 , 34 , 35 ]. This may mean Ontario could see a reduction in treatment volumes and the need for the interim funding measures in the coming months may be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, prescribers are challenged with balancing the risks and benefits of treating cancer patients who are also impacted, both directly and indirectly, by COVID-19. As countries try to contain the spread of COVID-19 and manage active COVID-19 infections, cancer patients may face treatment interruptions or delays in accessing standard diagnostic procedures and treatment modalities, including curative surgeries, radiation, and systemic therapies [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Designated COVID-19-restricted centers might potentially be better for performing cancer surgery, and periodic testing of involved healthcare staff is also warranted to mitigate disease transmission between hospital staff and patients. The need for designated COVID-19-free hospitals to offer continued cancer care was recommended by Restivo et al [ 14 ] after their initial observation of the pandemic in Italy and has also been recommended by others [ 12 , 15 ]. These facilities must implement standardized, mandatory preoperative testing pathways before patient admission.…”
Section: Discussionmentioning
confidence: 99%
“…32 Por su parte el NHS de Inglaterra reportó una disminución del 60% en las citas de quimioterapia para pacientes con cáncer en comparación con los niveles anteriores a COVID-19. 34 La revisión del estudio DATA-CAN que analizó los registros clínicos de más de 3 millones de adultos, demuestran caídas en las admisiones para quimioterapia similares (reducción del 45-66%). 17…”
Section: Terapia Sistémicaunclassified